Measuring Changes in Jaw Opening Forces to Assess the Degree of Improvement in Patients with Temporomandibular Disorders - Ratnayake, J.; Guan, G.; Polonowita, A.; Gray, A.R.; Loch, C.; Li, K.C.; Waddell, J.N.; Lyons, K.; Brunton, Paul (2022)
Background: Currently, the degree of improvement in patients with TMDs is measured through subjective questionnaires and clinical examination This study aimed to investigate the properties of an objective quantitative measure of jaw-opening forces to assess clinical improvement in temporomandibular disorder (TMD) patients following treatment. Methods: Baseline jaw-opening forces were recorded for TMD-patients (n = 62) and a comparison group of TMD-free participants (n = 56), using a jaw-opening forces measuring device. TMD patients were divided into three subcategories (myofascial pain, disc-displacement, and myofascial pain and disc-displacement combined) and received a combination of treatment for six months; meanwhile, TMD-free participants did not receive treatment. Jaw-opening forces for each participant in both groups were measured at their six-month review appointment. Results: Jaw-opening forces were reliable at baseline (single measure ICC 0.98, 95% CI 0.97–0.98, ICC ≥ 0.94 for all groups and subcategories). Jaw-opening forces increased in the TMD group following treatment at six-months (18.6 N at baseline and 32.4 N at six-months, p < 0.001) and did not change significantly in the TMD-free group (49 N at baseline and 48.3 N at six-months). There was a small improvement in the disc displacement group (27.8% higher forces, p = 0.002). However, the myofascial-pain and myofascial-pain-and-disc-displacement groups showed significant improvement following treatment (93.5% higher forces, p < 0.001; 91.1% higher forces, p < 0.001; respectively). Conclusion: This study demonstrated that the measurement of jaw-opening forces could potentially be used to assess the clinical improvement in TMD patients following diagnosis and treatment.